Pengaruh Terapi Murottal Al-Quran Terhadap Tekanan Darah Dan Frekuensi Denyut Jantung Pasien Pasca Operasi Dengan Anestesi Umum Di Rumah Sakit Umum Daerah Dr. Moewardi Surakarta - Nafi'ah, Rizka Zakiyyatun; , Arina Maliya S.Kep,M.Si.Med; , Enita Dewi, S.Kep, Ns., MN (2016)
Stress response during surgery and after surgery with all its consequences need to be feared because it can increase mortality and morbidity. One result of the stress response is hemodynamic changes, which can be seen in blood pressure and heart rate. High incidence of complications can be caused by blood pressure and heart rate. Change in the management of postoperative recovery in space conscious can use complementary therapies as a companion therapy. This study aims to determine the influence of murottal Al-Quran on blood pressure and heart rate. This research is a quantitative study with a pre experimental with non-equivalent control group design. Sample study was 30 patients surgery with general anesthesia in the Hospital Dr. Moewardi Surakarta with quota sampling technique. The collecting data using bed side monitor and data analysis t-test. Results of research by Independent sample t-test on systolic blood pressure values obtained p-value = 0.044, diastolic blood pressure with a p-value = 0.049, and the heart rate with a p-value = 0.432. Conclusions from this research is that there are differences in systolic blood pressure and diastolic patients post surgery with general anesthesia between treatment groups murottal Al-Quran with the group without murottal Al-Quran and there are no differences in heart rate of patients after surgery with general anesthesia between treatment groups murottal Al-Quran with the group without murottal Al-Quran. Suggestions for further research on the same theme should increase respondents more specific and homogeneous so that research results can be more accurate. Keywords: blood pressure, heart rate, murottal Al-Quran, post general anesthesia, post operative.